Event‐triggered H∞ control for switched interval type‐2 fuzzy systems under denial‐of‐service - Qu, Hanqing; Zhao, Jun (International journal of robust and nonlinear control, 2023)
This article focuses on the H∞$$ H_{∞ } $$ control problem for event‐triggered switched interval type‐2 (IT2) fuzzy systems under denial‐of‐service (DoS) attacks. For a switched IT2 fuzzy system subject to DoS attacks, we introduce an acknowledgment (ACK) mechanism to detect DoS attacks. With the help of the ACK detection scheme, we take the initiative to zero the input signal being attacked. In this way, when the system is being attacked, we need not consider issues of controller premise variables not being updated and the controller mode unmatched with the plant mode. Then, an event‐triggering scheme resilient to DoS is presented to reduce the bandwidth pressure of the network. Moreover, we design a sampled‐based switching law to not only achieve the stability of switched systems but also exclude the Zeno behavior of switchings. Sufficient conditions are proposed to guarantee the stability with the H∞$$ H_{∞ } $$ performance of switched IT2 fuzzy systems under DoS. Finally, we give two examples to testify the effectiveness of our results.